2015
DOI: 10.1111/pbi.12389
|View full text |Cite
|
Sign up to set email alerts
|

A petal‐specific InMYB1 promoter from Japanese morning glory: a useful tool for molecular breeding of floricultural crops

Abstract: These two authors contributed equally to this work. Keywords: floricultural crops,Ipomoea nil, molecular breeding, MYB, petal-specific promoter. SummaryProduction of novel transgenic floricultural crops with altered petal properties requires transgenes that confer a useful trait and petal-specific promoters. Several promoters have been shown to control transgenes in petals. However, all suffer from inherent drawbacks such as low petal specificity and restricted activity during the flowering stage. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…These results suggest that the CYP86A4 promoter induces increase of cuticle nanoridges and alters the resultant petal texture more effectively than the CYP77A6 promoter in floral organs, and that MIXTAlike TFs consistently induce nanoridge production in nanoridge-forming cells. Our observations regarding the petal adaxial surface are consistent with those of plants expressing MYB106-VP16 under the control of the petalspecific InMYB1_1kb promoter (Azuma et al 2016).…”
Section: Cuticle Accumulation On Floral Organssupporting
confidence: 88%
“…These results suggest that the CYP86A4 promoter induces increase of cuticle nanoridges and alters the resultant petal texture more effectively than the CYP77A6 promoter in floral organs, and that MIXTAlike TFs consistently induce nanoridge production in nanoridge-forming cells. Our observations regarding the petal adaxial surface are consistent with those of plants expressing MYB106-VP16 under the control of the petalspecific InMYB1_1kb promoter (Azuma et al 2016).…”
Section: Cuticle Accumulation On Floral Organssupporting
confidence: 88%
“…Ectopic expression often results from overexpression of the TFs using constitutive promoters or, in a few examples, is made dependent of endogenously regulated factors as, e.g. ripening (47), senescence (49) or tissue specific factors (5052). A step forward in transcriptional control would involve connecting endogenous pathways (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Elongation factor-1α (AtEF1) was used as an internal control. Total RNA was isolated from stage-3 flower buds (Azuma et al 2016b) using Trizol (Thermo Fisher Scientific, MA, USA) and reverse-transcribed using PrimeScript RT reagent Kit with gDNA Eraser (TaKaRa, Shiga, Japan). Real-time PCR was carried out using obtained cDNA and SYBR Premix EX Taq (TaKaRa, Shiga, Japan) with StepOnePlus real-time PCR system (Thermo Fisher Scientific, MA, USA).…”
Section: Measurement Of Promoter Activitymentioning
confidence: 99%
“…In the InMYB1_403b::GUS or InMYB1_332b::GUS transgenic plants, it was decreased to 50% or 30%, respectively, and no GUS staining was observed in the InMYB1_200b::GUS and InMYB1_140b::GUS transgenic plants (Figure 3). We previously reported that some kinds of cis-element such as CAAT-box, which increases promoter activity, exist in the 1023-332 bp upstream region of InMYB1 (Azuma et al 2016b). Although the petal-specific promoter activity became weaker and unstable by deletion of the several cis-elements, the 332 bp upstream region of InMYB1 still functioned as a petalspecific promoter.…”
Section: Identification Of the Petal-specific Region By Deleting The mentioning
confidence: 99%